Correlation between permanent teeth eruption and nutrition status of 6-7-years-old children - Lailasari, Della; Zenab, Yuliawati; Herawati, Erna; Wahyuni, Indah Suasani (Padjadjaran Journal of Dentistry, 2018)
Introduction: Tooth eruption is influenced by various factors, one of them is nutritional factors. This study was aimed to obtain information regarding the relationship between the number of permanent teeth erupted with nutritional status in 6-7-years-old children. Methods: This research was cross-sectional and correlational data analysis. The study was conducted towards as much as 57 children aged 6-7 years old. The sampling method was the purposive sampling technique conducted in Tanjungsari 2 State Elementary School, Sumedang Regency. The nutritional status was calculated based on the Body Mass Index (BMI) according to age from the anthropometric measurements of body weight and height. Assessment of nutritional status was performed using the WHO Anthroplus® v1.0.4 application. Statistical analysis was performed using the Spearman correlation test and Mann-Whitney difference test. Results: The correlation test has obtained the value of ρ = 0.037, which showed a significant relationship between the number of permanent teeth erupted with nutritional status of 6-7-years-old children. The Spearman correlation coefficient has obtained the value of r = 0.277, thus showed the weak strength and positive direction of the correlation. Conclusion: There is a relationship between the nutritional status and the number of permanent teeth erupted in children aged 6-7 years old in the Tanjungsari Sub-district of Sumedang Regency. The higher the nutritional status of a child, the more number of permanent teeth erupted.